A data-driven framing of player and team performance in U.S. women's soccer - Narayanan, S.; Pifer, N. D. (Frontiers in Sports and Active Living, 2023)
Introduction: In establishing historical benchmarks for success on the pitch and striving to achieve parity off it, the United States Women's National Team (USWNT) and the National Women's Soccer League (NWSL) have long served as standard bearers for professional women's soccer around the globe. However, off-field dilemmas and incessant juxtapositions to men's soccer frequently overshadow the elements that make U.S. women's soccer unique; that is, in the quest to expose and rid the women's game of blatant misconduct, discriminatory practices, and negative stereotypes, relatively little attention has been devoted to performance features that separate the U.S. women's soccer product from its competition. Because many of the issues hindering the progress of women's soccer are rooted in media and managerial practices that marginalize or ignore its positive traits, a need exists for analyses that will properly identify its innate characteristics and competitive advantages so that media members, managers, and fans can accurately frame their perceptions of women competing in the sport.